Cardiac remodeling and pre‐eclampsia: an overview of microRNA expression patterns. (4th September 2018) - Mohseni, Z.; Spaanderman, M. E. A.; Oben, J.; Calore, M.; Derksen, E.; Al‐Nasiry, S.; de Windt, L. J.; Ghossein‐Doha, C.
ABSTRACT: Pre‐eclampsia (PE) is strongly associated with heart failure (HF) later in life. During PE pregnancy, the left ventricle undergoes concentric remodeling which often persists after delivery. This aberrant remodeling can induce a molecular signature that can be evaluated in terms of microRNAs (miRNAs) and which may help to explain the associated increased risk of HF. For this review, we performed a literature search of PubMed (National Center for Biotechnology Information), identifying studies on miRNA expression in concentric remodeling and on miRNA expression in PE. The miRNA data were stratified based on origin (isolated from humans or animals and from tissue or the circulation) and both datasets compared in order to generate a list of miRNA expression patterns in concentric remodeling and in PE. The nine miRNAs identified in both concentric remodeling and PE‐complicated pregnancy were: miR‐1, miR‐18, miR‐21, miR‐29b, miR‐30, miR‐125b, miR‐181b, miR‐195 and miR‐499‐5p. We found five of these miRNAs (miR‐18, miR‐21, miR‐125b, miR‐195 and miR‐499‐5p) to be upregulated in both PE pregnancy and cardiac remodeling and two (miR‐1 and miR‐30) to be downregulated in both; the remaining two miRNAs (miR‐29b and miR‐181b) showed upregulation during PE but downregulation in cardiac remodeling. This innovative approach may be a step towards finding relevant biomarkers for complicated pregnancy and elucidating their relationship with remote cardiovascular disease. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.